The post-Soviet handbook : a guide to grassroots organizations and Internet resources - Ruffin, M. Holt; Ruffin, M. Holt (Center for Civil Society International in association with University of Washington Press, 1999)
"This thoroughly revised edition of The Post-Soviet Handbook documents the variety of grassroots efforts in Russia, Ukraine, and five other nations of post-Soviet Eurasia, providing concise descriptions and accurate contact information for these diverse organizations. Many of the new entries represent projects based in provincial centers, reflecting powerful trends in post-Soviet societies toward autonomy and decentralization. Internet users will find a wealth of new resources. A new element is the inclusion of projects based in Canada. Whether the issues are the environment, the disabled, the excesses of "wild capitalism," human rights, or ethnic conflict, The Post-Soviet Handbook shows how grassroots self-organization accomplishes real change."--Jacket.